2020
DOI: 10.3399/bjgpopen20x101003
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the patient voice in gout: a quantitative study conducted in Europe

Abstract: BackgroundAlthough commonly diagnosed, gout often remains a poorly managed disease. This is partially due to a lack of awareness of the long-term effect of gout among patients and healthcare professionals.AimTo understand unmet needs for patients and provide insight into achieving better treatment.Design & settingA quantitative online questionnaire collected from 1100 people with gout from 14 countries within Europe.MethodPatients were recruited to complete an online survey via healthcare professional (HCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…3 A quantitative survey of 1100 people with gout also reported a reduction in perceived treatment satisfaction as the number of flares increased. 12 However, two-thirds of patients who experienced 5 or more flares in the previous year also reported satisfaction with treatment, 12 highlighting the importance of factors other than flare frequency that may be driving patient-perceived treatment efficacy. Pain severity appeared to be the least influential of the 3 factors perceived as indicative of treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…3 A quantitative survey of 1100 people with gout also reported a reduction in perceived treatment satisfaction as the number of flares increased. 12 However, two-thirds of patients who experienced 5 or more flares in the previous year also reported satisfaction with treatment, 12 highlighting the importance of factors other than flare frequency that may be driving patient-perceived treatment efficacy. Pain severity appeared to be the least influential of the 3 factors perceived as indicative of treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are studies reporting discordance between patients and physicians on a presence of a gout flare, with a rate as high as 30% [ 48 ]. Furthermore, patients report poor follow-up and disease monitoring from their physicians, as well as a lack of discussion about treatment options [ 38 ]. Patients tend to take prescribed treatments transiently [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, younger patients have a greater time to diagnosis, and this may negatively affect their future health. Moreover, 25% reported that a family member has retired or got fired due to gout [ 38 ]. Illness should be observed not only by its seriousness and mortality risk, but also as its effect on quality of life, cost for health care systems and individuals, and associated comorbidities and their effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations